Does preoperative physiotherapy improve outcomes in patients undergoing total knee arthroplasty? A systematic review. (4th February 2022) - Vasileiadis, Dimitrios; Drosos, Georgios; Charitoudis, Georgios; Dontas, Ismene; Vlamis, John
Abstract: Objective: To systematically review the scientific literature and to investigate the effectiveness of preoperative rehabilitation on subjective and objective outcomes after total knee arthroplasty (TKA) when compared with patients in a control group. Data sources: A search was conducted in PubMed, PubMed Central, Embase, Cochrane Library and Physiotherapy Evidence Database databases in May 2021. Study selection: randomized controlled trials (RCTs) were reviewed if they compared a preoperative physiotherapy exercise intervention with no intervention group for patients undergoing TKA for severe Osteoarthritis (OA). A total of 24 RCTs were included at the end of the evaluation process. By the end of the evaluation process, a total of 24 RCTs were included. Data extraction: Two authors independently screened the literature, extracted data, and assessed the quality of included studies. The outcomes were knee extension, knee flexion, pain Visual Analogue Scale (VAS), overall Western Ontario and McMaster Universities OA Index, 6 min walking test, and Timed Up and Go test. Results: The majority of the studies included in this systemic review demonstrated a comparable trend of long‐term postoperative improvement of knee extension strength, VAS, range of movement and functional scores, and those of quality of life between two groups. Many studies showed a significant improvement in terms of preoperative pain, length of hospital stay and functional performance shortly after the operation, but all studies failed to show a prolonged effect on knee motion or patient function between 3 and 12 months. Conclusions: Low to moderate evidence from mostly small RCTs demonstrated that preoperative physiotherapy interventions reduce pain and improve functional performance for patients with knee OA prior shortly after the TKA.